Laboratory Evaluation of Insecticides as Contact Sprays against Forest Pests. I-Teak Skeletoniser: Pyraust A Machaeralis Walker (Lepidoptera: Pyralidae) - Singh., Pratap; Gupta, B. K. (Indian Forester, 1978)
Twenty insecticides were tested as contact sprays, against the 3rd instar larvae of Pyrausta Machaeralis. Out of these four insecticides viz., Monocrotophos, Chlordimeform, Quinalphos and Anthio proved most effective in comparision to DDT (WP) while, Acephate and Carbaryl also proved 15.314 and 8544 times more effective than DDT(WP). Rest of the fourteen insecticides can be put according to their effectiveness in descending order as Fenitrothion, Dichlorvos, Dieldrin, Dimethoate. Cythion, Endrin, Gamma BHC, Endosulfan, Leptophos,Maluthion, Aldrin, Ambithion, DDT (WDP) and DDT(WP).